Dispensation of antiretroviral therapy and methadone maintenance therapy at the same facility in a low‐barrier setting linked to optimal adherence to HIV treatment - Mohd Salleh, Nur Afiqah; Fairbairn, Nadia Souhalya; Nolan, Seonaid; Barrios, Rolando; Shoveller, Jeannie A.; Richardson, Lindsay A.; Milloy, Michael John (Wiley, 2019)
Objectives: We sought to examine the association between dispensation of methadone maintenance therapy (MMT) and antiretroviral therapy (ART) at the same facility, across multiple low-barrier dispensing outlets, and achieving optimal adherence to ART among people who use illicit drugs (PWUD). Methods: We used data from the AIDS Care Cohort to Evaluate Exposure to Survival Services (ACCESS) study, a long-running study of a community-recruited cohort of HIV-positive PWUD, linked to comprehensive HIV clinical records in Vancouver, Canada, a setting of no-cost, universal access to HIV care. The longitudinal relationship between MMT-ART dispensation at the same facility and the odds of ≥ 95% ART adherence was analysed using multivariable generalized linear mixed-effects modelling. We conducted a further analysis using a marginal structural mode with inverse probability of treatment weights as a sensitivity analysis. Results: This study included data on 1690 interviews of 345 ART- and MMT-exposed participants carried out between June 2012 and December 2017. In the final multivariable model, MMT-ART dispensation, compared with nondispensation at the same facility, was associated with greater odds of achieving ≥ 95% adherence [adjusted odds ratio (AOR) 1.56; 95% confidence interval (CI) 1.26–1.96]. A marginal structural model estimated a 1.48 (95% CI 1.15–1.80) greater odds of ≥ 95% adherence among participants who reported MMT-ART dispensation at the same facility compared with those who did not. Conclusions: The odds of achieving optimal adherence to ART were 56% higher during periods in which MMT and ART medications were dispensed at the same facility, in a low-barrier setting. Our findings highlight the need to consider a simpler integrated approach with medication dispensation at the same facility in low-threshold settings. © 2019 British HIV Association